A2.30 Common variants on XQ28 conferring risk for rheumatoid arthritis in Tunisian and French populations. (13th February 2015) - Khalifa, O; Balandraud, N; Lambert, N; Martin, M; Senechal, A; Genevieve, D; Picard, C; Lefranc, G; M'madi, B; Pardoux, E; Mahjoub, T; Apparailly, F
Abstract : Background and objectives: Rheumatoid arthritis (RA) is a systemic autoimmune disease characterised by a chronic destructive inflammation in synovial joints that is about three times more common in women than in men. Investigations into RA genetics have identified several susceptibility loci. Among these, multiple single-nucleotide polymorphisms (SNPs) at an X chromosome locus harbouring IRAK1 and TMEM187 have previously been shown to be associated with susceptibility to RA in Greek, Chinese, and Korean populations. The present study aimed at investigating the association between critical polymorphisms in Xq28, from rs1059702 (C/T) and rs1059703 (C/T) in IRAK1 through rs13397 (A/G) in TMEM187 with risk for RA in two novel populations: Tunisian and French. In addition, the present study aimed at comparing the differences in genotypic distribution in both populations. Material and methods: A case–control study of 493 RA patients and 507 healthy controls age and sex matched was conducted in both Tunisian and French. All RA patients were ACPA positive. DNA was isolated from total blood using standard phenol chloroform method. All subjects were genotyped for the three polymorphisms using a direct sequencing with the BigDye Terminator v3.1 Cycle Sequencing Kit (Applied Biosystems). The genotype distribution, haplotype analysis, and the linkage disequilibrium (LD) were analysed using the Bayesian method, and PLINK 1.07 and Haploview 4.2 softwares, respectively. Results: The three polymorphisms respected Hardy-Weinberg equilibrium, both in Tunisian and French populations. The associations between both IRAK1 rs1059703 and TMEM187 rs13397 polymorphisms and RA susceptibility were found (p < 0.001 and p = 0.004, respectively) in women, but not in men. The genotype CC of rs1059703 represented a protective factor for RA (OR = 0.29, 95% CI = 0.17–0.50). Linkage disequilibrium between the 3 SNPs was weak (D = 8–16). There were 5 haplotypes with a frequency higher than 5%, constructed from the Xq28 polymorphisms. Haplotype GTC was associated with decreased risk for RA (p = 0.00075), whereas the haplotype ACC was significantly associated with increased risk for RA (p < 0.001). Correlation analyses with clinical and biological parameters are in progress. Conclusion: Our case-control study replicated for the first time the association of the Xq28 chromosomal region with RA risk in Tunisian and French populations, and suggested that RA susceptibility is associated with rs1059703 polymorphism in IRAK1 and rs13397 polymorphism in TMEM187 only for female patients. These data further support the involvement of X chromosome in RA susceptibility.